Penguatan literasi budaya Minangkabau dalam kegiatan Sapakan Pagelaran Alek Kesenian Anak Nagari Andaleh Baruh Bukik - Apriani, Wulan; Winoto, Yunus; CMS, Samson (Jurnal Informatio, 2024)
Cultural literacy is an essential skill that enables individuals to understand and appreciate various cultural aspects in a multicultural context. In an increasingly interconnected era of globalization, cultural literacy plays a role in strengthening local identity while addressing the challenges of cultural homogenization. This study explores the reinforcement of Minangkabau cultural literacy through the Sapakan Alek Kesenian event in Nagari Andaleh Baruh Bukik, West Sumatra. The event serves as a conscious effort to preserve local traditions, including arts, dance, and traditional games, amid the currents of modernization. This research employs a qualitative method with a case study approach, involving participatory observation, in-depth interviews, and document analysis. The findings reveal that Sapakan Alek Kesenian not only strengthens social bonds among community members but also enhances the understanding and appreciation of Minangkabau cultural heritage among the younger generation. The main challenges encountered include the influence of globalization and changes in the curriculum that have removed Minangkabau Cultural Studies from formal education. This study recommends integrating cultural activities into education and fostering collaboration between the government, communities, and traditional institutions to strengthen cultural literacy outside of schools. The research provides practical insights for cultural preservation and the reinforcement of local identity in the global era.